Rural development in India:Policies and initiatives - Reddy A.vinayak (ed.); Charyulu, M.Yadagira (ed.) (New Delhi, 2008)
Rural infrastructure in India, though much more improved than prior to economic reforms, is not commensurate with emerging challenges of globalization to the rural economy. In the face of increasing consumerism, traditional rural activities are loosing their importance. Rural skills are either untapped or underutilized. The upgrade of rural technologies has not been taking place satisfactorily in order to meet the needs of unemployed rural youth. The rural youth in general and the educated youth in particular are deprived of employment opportunities due to the digital divide. Also, rural artisans are not finding a proper place in the rural economic arena due to inadequate opportunities to improve upon their worth. Without proper credit, raw material, and market, rural artisans are not in a position to cope with emerging challenges. Tragically, this is leading some rural artisans, as well as farmers, to commit suicide. This book covers the major issues pertaining to the impact of globalization on rural sector of India.
Keywords: Development Rural